Bloodstream Infections in Critical Care Units in England, April 2017 to March 2023: Results from the First Six Years of a National Surveillance Programme - Olivia D. Conroy; Andrea Mazzella; Hannah Choi; Jocelyn Elmes; Matt Wilson; Dimple Y. Chudasama; Sarah M. Gerver; Miroslava Mihalkova; Andrew Rhodes; A. Peter R. Wilson; Nicholas Brown; Jasmin Islam; et al. (Microorganisms)
Background: Patients in critical care units (CCUs) are at an increased risk of bloodstream infections (BSIs), which can be associated with central vascular catheters (CVCs). This study describes BSIs, CVC-BSIs, organism distribution, percentage of antimicrobial resistant (AMR) organisms, and case fatality rates (CFRs) over the first six years of a voluntary national CCU surveillance programme in England. Methods: Surveillance data on BSIs, CVCs, and bed-days between 04/2017 and 03/2023 for adult CCUs were linked to mortality and AMR data, and crude rates were calculated. Results: The rates of CCU-BSIs and CCU-CVC-BSIs were stable for the first three years (3.6 and 1.7 per 1000 bed-days in 2019/20), before increasing by 75% and 94% in 2020/21, respectively, and returning to near pre-pandemic levels by 2022/23. Gram-negative bacteria accounted for 50.3% of all CCU-BSIs, followed by Gram-positive bacteria (39.6%) and Candida spp. (8.6%). Klebsiella spp. saw increases in percentage AMR, whereas other organisms saw declines or similar levels. The overall CFR was 30.2%. Conclusions: BSI incidence in CCUs remained stable across the study period, except for an increase in 2020/21 which reverted by 2022/23. These data provide a benchmark for CCUs and give insight into long-term AMR patterns where comparable national data are limited.